2011
DOI: 10.3109/02713683.2011.556300
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tempol on Diabetes-Induced Decreases in Retinal Blood Flow in the Mouse

Abstract: The antioxidant tempol provides partial improvements in retinal microvascular hemodynamics early in the progression of STZ-induced diabetes in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 26 publications
2
22
2
Order By: Relevance
“…They are also similar to other reported reductions in F values in STZ-diabetic mice. 3236 Had these investigators measured O 2A , it is likely that they would have found decreases in DO 2 similar to the decrease of 43% in the current study. These defective DO 2 and F responses in diabetes likely correspond to the well-known impaired autoregulation seen in humans with diabetes.…”
Section: Discussionsupporting
confidence: 57%
“…They are also similar to other reported reductions in F values in STZ-diabetic mice. 3236 Had these investigators measured O 2A , it is likely that they would have found decreases in DO 2 similar to the decrease of 43% in the current study. These defective DO 2 and F responses in diabetes likely correspond to the well-known impaired autoregulation seen in humans with diabetes.…”
Section: Discussionsupporting
confidence: 57%
“…Similar to early human DR, we observe significant decreases in retinal blood flow rates in the initial weeks of hyperglycemia in diabetic rats and mice (Lee and Harris 2008; Lee et al, 2008; Wright and Harris 2008; Wright et al, 2009; Wang et al, 2010; Wang et al, 2011; Yadav and Harris 2011). The magnitude of the decrease within the first several weeks of developing hyperglycemia in rodents is ~25-40%, very similar to the change seen in early human DR.…”
Section: Introductionsupporting
confidence: 63%
“…In the larger vessels of the healthy retina, centerline velocity is approximately 30 mm ⁄ s (Nagaoka & Yoshida 2006;Nagaoka et al 2009;Yadav & Harris 2011). Fringe washout, the phenomenon responsible for the decrease in SD-OCT signal at high flow velocities, becomes significant at flow velocities above 34 mm ⁄ s when the direction of flow is <5 degrees away from the perpendicular to the line of sight (Hendargo et al 2011).…”
Section: Discussionmentioning
confidence: 99%